2017
DOI: 10.1080/03004430.2017.1324433
|View full text |Cite
|
Sign up to set email alerts
|

Preschool children’s knowledge about the environmental impact of various modes of transport

Abstract: This study explored Swedish preschool children's knowledge about the environmental impact of various transport modes, and investigated whether or not eco-certification has any role to play in relation to this knowledge. Additionally, this study examined children's perceived sources of knowledge. Using illustrations and semi-structured questions, 53 children, aged five to six years, from six eco-certified and six non-eco-certified preschools were interviewed. Qualitative and quantitative data were analysed usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 34 publications
0
18
1
3
Order By: Relevance
“…These findings are consistent with those of previous studies reporting that children who participated in whole-school programmes, such as eco-schools or schools that promote a healthy lifestyle, had a deeper understanding of these issues; furthermore, they learned about various global and local issues related to sustainability with support of their teachers (Davis, 2005;Davison, Davison, Reed, Halden, & Dillon, 2003;Lewis, Mansfield, & Baudains, 2010;Mackey, 2012). Nevertheless, two previous studies that compared eco-certified and non-eco-certified preschools in terms of children's knowledge and practices of environmental and sustainability issues using statistical analysis did not find any statistically significant differences (Borg, et al, 2017a(Borg, et al, , 2017b. Therefore, it is important to conduct a large-scale study of sufficient statistical power to investigate whether eco-certification plays any role in developing children's knowledge, attitudes and behaviours of particular relevance to a sustainable society.…”
Section: Preschool Children's Level Of Justificationsmentioning
confidence: 92%
See 1 more Smart Citation
“…These findings are consistent with those of previous studies reporting that children who participated in whole-school programmes, such as eco-schools or schools that promote a healthy lifestyle, had a deeper understanding of these issues; furthermore, they learned about various global and local issues related to sustainability with support of their teachers (Davis, 2005;Davison, Davison, Reed, Halden, & Dillon, 2003;Lewis, Mansfield, & Baudains, 2010;Mackey, 2012). Nevertheless, two previous studies that compared eco-certified and non-eco-certified preschools in terms of children's knowledge and practices of environmental and sustainability issues using statistical analysis did not find any statistically significant differences (Borg, et al, 2017a(Borg, et al, , 2017b. Therefore, it is important to conduct a large-scale study of sufficient statistical power to investigate whether eco-certification plays any role in developing children's knowledge, attitudes and behaviours of particular relevance to a sustainable society.…”
Section: Preschool Children's Level Of Justificationsmentioning
confidence: 92%
“…The interviewer also used a cuddly puppet, some toys and a special sitting mat with a picture of two puppies to initiate a friendly and informal conversation with the child. The cuddly puppet (a teddy bear that was named Kim) was used for asking children questions as though the puppet was their friend (for more information about the interview instrument, see Borg, 2017;Borg, Winberg, & Vinterek, 2017a, 2017b. Each interview took approximately 5-10 minutes.…”
Section: Data Collectionmentioning
confidence: 99%
“…This was done to introduce the term "nature". We used the term "nature" (natur in Norwegian) instead of "environment", since previous research conducted in Sweden has shown that the word "environment" (miljø in Norwegian, miljö in Swedish) is unknown to most kindergarten children [34], while they are more familiar with the term "nature". Then we asked the children whether they considered humans as being part of nature.…”
Section: Semi-structured Interviews With Four Photos-what Is Nature?mentioning
confidence: 99%
“…Transport emissions have a major impact on the worldwide climate problem [1,2]. The World Health Organization (WHO) even declared the transportation sector as the fastest growing contributor to climate emissions, as it (among other factors) leads to long-lived carbon dioxide emissions and short-lived black carbon [3].…”
Section: Introductionmentioning
confidence: 99%
“…The World Health Organization (WHO) even declared the transportation sector as the fastest growing contributor to climate emissions, as it (among other factors) leads to long-lived carbon dioxide emissions and short-lived black carbon [3]. This affects people's futures, but also their current quality of life, as it has an impact on health (e.g., automated transport decreases a person's physical activity level and it degrades the air-quality due to polluted emissions), safety (e.g., more cars on the road lead to more traffic and accidents), and well-being (e.g., traffic leads to more noise pollution) [1,4]. The WHO calculated that air pollution is even the biggest environmental risk to health, and showed that in 2016, 4.2 million deaths could globally be attributed to ambient air pollution [5].…”
Section: Introductionmentioning
confidence: 99%